Efeito do tratamento com quercetina sobre a nefropatia diabética em camundongos teroscleróticos - Gomes, Isabele Bezerra dos Santos (2010)
Dyslipidemia contributes to the increased risk of death and morbidity in patients with diabetes by accelerating macro and microvascular disease. Furthermore, clinical observations have suggested that hyperlipidemia is a contributory factor to the progression of diabetic renal disease. Quercetin has been reported to have many beneficial effects on human health, including cardiovascular protection and antiinflammatory effects. Considering the deleterious effects of diabetes the aim of this study was to evaluate the effect of quercetin on diabetic nephropathy in C57BL/6 and apoE deficient mice (apoE(-/-)) with experimental diabetes. Male mice C57 and apoE(-/-) 8-week-old were separated in groups: control, diabetic vehicle and diabetic treated with quercetin. Diabetes was induced by injection of streptozotocin (STZ, 100mg/kg/day, i.p.) diluted in citrate buffer, for 3 days, the vehicle group received only citrate buffer. The STZ-treated animals with glycemia lower than 250mg/dL were excluded from the study. Six weeks after diabetes induction, the animals were divided in vehicle and quercetin groups, which received vehicle (soy oil), or a suspension of quercetin (10 mg/kg, daily) orally during 4 weeks. In the 10th week mice were euthanized, blood was collected for biochemical dosage; urine was collected for dosage of creatinine and determination of proteinuria and the kidneys were fixed for histological analysis. All procedures were approved by the Animal Ethics Committee for Use of Animals of EMESCAM College of Health Sciences (013/2007). Data are expressed as mean ± SEM. Statistical analysis was performed using two way ANOVA followed by Fisher´s post hoc test and p<0.05 was considered significant. Diabetic mice showed significant increase in blood glucose, polyuria and proteinuria compared with control group. Diabetic groups also exhibited renal dysfunction, as evidenced by increased plasma creatinine, plasma urea and proteinuria. The histological evaluation of diabetic nephropathy was observed a increase in glomerular matrix deposition and glomerular hypertrophy. The treatment with quercetin decreased the plasma glucose level of both diabetic groups, as well as reduced high plasma concentrations of triglycerides and creatinine. The evaluation of renal function showed an improved creatinine clearance and a decreased proteinuria. In histological results was observed ameliorate in glomerular tuft size and a decrease of glomerular matrix deposition in diabetic groups. Reactive oxygen species play a key role in the pathophysiological processes of renal diseases. Thus, antioxidants, as quercetin, are expected to decrease the vulnerability of the kidney to oxidative challenges. Quercetin demonstrated a beneficial antidiabetic effect and ameliorated diabetic renal damage.